Does uncertainty cause inertia in decision making?: an experimental study of the role of regret aversion and indecisiveness (2017)
Previous research has shown that individual decision making is often characterized by inertia—that is, a tendency for decision makers to choose options that maintain the status quo. In this study, I conduct a laboratory experiment to investigate two potential determinants of inertia in uncertain environments: (i) regret aversion and (ii) ambiguity-driven indecisiveness. I use a between-subjects design with varying conditions to identify the effects of these two mechanisms on choice behavior. In each condition, participants choose between two simple real gambles, one of which is the status quo option. The findings indicate that regret aversion and ambiguity-driven indecisiveness are equally important determinants of inertia, which in turn plays a major role in individual decision making.